Analysis of the Effect of Infrastructure and the Tourism Sector on Gross Regional Domestic Product (GRDP) Per Capita in Regencies/Cities of East Nusa Tenggara Province During 2020–2023 - Mesya Hafif Wal’Azra; Yuni Prihadi Utomo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates how infrastructure development and the tourism industry contribute to regional economic performance in East Nusa Tenggara Province. The study utilizes panel data from 22 regencies/cities covering the 2020–2023 period and employs panel data regression analysis using the Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM) approaches. The selection of the most suitable model was determined through the Chow test and Hausman test. The findings reveal that the Fixed Effect Model (FEM) provides the best fit and possesses a strong capability in explaining the model. The partial test results show that regional government expenditure (APBD), the number of banking institutions, and the number of domestic tourists have a significant influence on GRDP per capita. However, APBD and the number of banks show a negative relationship, suggesting that fiscal capacity and financial institutions have not yet been optimally directed toward productive economic activities. In contrast, domestic tourism has a positive and significant effect, indicating its important role in driving regional economic performance. These findings imply that improving the effectiveness of public spending, strengthening financial intermediation, and optimizing tourism potential are essential to enhance regional economic growth. Therefore, local governments are encouraged to allocate budgets more productively, improve access to financing for the real sector, and intensify domestic tourism development strategies.